2009
DOI: 10.1097/smj.0b013e3181a52117
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Internet for Health Information Among Primary Care Patients in Rural West Texas

Abstract: Our findings showed a much lower rate of internet use for medical/health information compared with a 2006 nationwide survey. This finding suggests that promoting health/medical information through websites or other on-line resources might not be the most effective way to reach a majority of patients in remote, rural or border areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
3
4
0
Order By: Relevance
“…Our findings align with studies in other chronic diseases, which reveal inconsistency in website use, but self-reported or measured use has been noted to range from approximately 10-40% of those queried [20-22]. Adults in the United States living with chronic disease are significantly less likely than healthy adults to have access to the Internet (62% vs 81%), but once online, those with chronic disease are more likely to use social media and online tools to share information and obtain support from their peers [23].…”
Section: Discussionsupporting
confidence: 89%
“…Our findings align with studies in other chronic diseases, which reveal inconsistency in website use, but self-reported or measured use has been noted to range from approximately 10-40% of those queried [20-22]. Adults in the United States living with chronic disease are significantly less likely than healthy adults to have access to the Internet (62% vs 81%), but once online, those with chronic disease are more likely to use social media and online tools to share information and obtain support from their peers [23].…”
Section: Discussionsupporting
confidence: 89%
“…This same iterative process was used in the development of the Safe Kidney Care Cohort study (SKC) website (http://www.safekidneycare.org), which provides information to patients, family members and providers, on topics relevant to patient safety in CKD [33]. After one year of follow-up, approximately 29% (n = 31) of SKC participants who were invited to visit the website (n = 108) did so, [34] which corroborates with other studies of website usage, revealing that approximately one third of study participants will visit a website when asked [35,36]. …”
Section: Reviewsupporting
confidence: 65%
“…Preliminary studies suggest that rural residents are less likely to search the Internet for general health information. [23][24][25] Much less is known regarding online searches for mental health information, although early findings from Australian studies suggest that Internet resources have high potential value for rural populations. 26 The purpose of this study was to investigate reactions to healthrelated information online in rural and nonrural adults, using data from the Pew Internet and American Life Project.…”
Section: Introductionmentioning
confidence: 99%